Management Based on Multicultural Islamic Educational - Tamimi, Muhyiddin Tohir; Maulana, Ade Irfan; Aziz, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to identify, analyse, and describe in depth the educational management model implemented at the Subulussalam Modern Islamic Boarding School (PPMS), Kresek, Tangerang, Banten, in internalising the values of multicultural Islamic education. PPMS, with its composition of students from various regions, is seen as an ideal social laboratory. The primary data are: Head of the Islamic Boarding School, teachers, and students of PPMS, and the data analysis techniques in this study are: Data condensation, data presentation, and drawing conclusions. The main results of the study indicate that multicultural management at PPMS is implemented informally but structurally through three pillars: 1) Integration of the values of Ukhuwah Islamiyah, Wathaniyah, and Basyariyah into the Tahfidz Al-Qur'an curriculum and religious subjects, 2) A heterogeneous boarding school policy (ethnically mixed room system) to facilitate intensive 24-hour interaction, and 3) The exemplary behaviour of Kiai and Ustadz/Ustadzah as models of tasamuh (tolerance) and ta'awun (mutual cooperation). In conclusion, management based on multicultural Islamic values at PPMS is effective in creating a harmonious and inclusive educational ecosystem, equipping students with spiritual and social intelligence that prepares them to face the challenges of global and domestic diversity. This study recommends the formalisation of this model as a management guide for other Islamic educational institutions.